Estudio de buenas prácticas turísticas para la hostería "cabañas bird planet", ubicada en el barrio Los Guayabales, parroquia Mindo, cantón San Miguel de los Bancos, provincia de Pichincha - Miño Escobar, Bernarda Alexandra (2016)
The Study of Good Practices in Tourist collecting information have allowed evaluating current conditions Hosteria Bird Planet; methodologies proposed as Rainforest Alliance and distinctive "Q" prioritizing the critical nodes in each of the methodologies mentioned; the first methodology was assessed using the MASTER technical tool. As a result notes that partially meets the parameters evaluated and therefore suggested in some for improvement in all its processes through each level. The second methodology for its part emphasizes quality tourism through business management played so far Bird Planet, just as rating parameters throwing favorable results were evaluated since it obtained the mark "Q" in the 2015 obtaining the No. 21. This evaluation was the ratification of its management during this year (2016); in some parameters it must improve so many things suggested.